2022
DOI: 10.1016/j.mgene.2022.101014
|View full text |Cite
|
Sign up to set email alerts
|

Severity of coronavirus disease 19: Profile of inflammatory markers and ACE (rs4646994) and ACE2 (rs2285666) gene polymorphisms in Iraqi patients

Abstract: Susceptibility to coronavirus disease 2019 (COVID-19) and disease severity has recently been associated with inflammatory markers and genetic polymorphisms of ACE (angiotensin-converting enzyme) and ACE2 genes, but the evidence has been inconclusive. This case-control study (99 COVID-19 patients and 96 controls) sought to assess the significance of age, C-reactive protein (CRP), neutrophil-to-lymphocyte ratio (NLR) and SARS-CoV-2 RT-PCR cycle threshold (Ct) in seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 51 publications
4
19
0
Order By: Relevance
“…Individuals with a D/D genotype were shown to have a higher incidence of pulmonary embolism and increased mortality rates, possibly due to increased levels of serum ACE [ 19 , 27 , 28 ]. This differs from our outcomes, otherwise consistent with other studies that found no association between the I/D polymorphism and disease severity [ 17 , 20 , 21 ]. One of the AGTR2 polymorphisms (rs1914711) was shown to increase the risk of severe COVID-19 in the Mayan population [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Individuals with a D/D genotype were shown to have a higher incidence of pulmonary embolism and increased mortality rates, possibly due to increased levels of serum ACE [ 19 , 27 , 28 ]. This differs from our outcomes, otherwise consistent with other studies that found no association between the I/D polymorphism and disease severity [ 17 , 20 , 21 ]. One of the AGTR2 polymorphisms (rs1914711) was shown to increase the risk of severe COVID-19 in the Mayan population [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, a protective role of A allele-related increase in ACE2 has been suggested, as it could help counterbalance the effects of increased Ag II resulting from RAAS dysregulation [ 20 ]. Nonetheless, in line with our results, several studies found no association with disease susceptibility or severity [ 17 , 21 , 22 ]. ACE insertion/deletion polymorphisms (rs4646994 and rs179752) have also been linked to COVID-19 severity.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations